Three paths to feeling just: how managers grapple with justice conundrums during organizational change - Zwank, Julia (Journal of business ethics, 2023)
Managers tasked with organizational change often face irreconcilable demands on how to enact justice - situations we call justice conundrums. Drawing on interviews held with managers before and after a planned large-scale change, we identify specific conundrums and illustrate how managers grapple with these through three prototypical paths. Among our participants, the paths increasingly diverged over time, culminating in distinct career decisions. Based on our findings, we develop an integrative process model that illustrates how managers grapple with justice conundrums. Our contributions are threefold. First, we elucidate three types of justice conundrums that managers may encounter when enacting justice in the context of planned organizational change (the justice intention-action gap, competing justice expectations, and the justice of care vs. managerial-strategic justice) and show how managers handle them differently. Second, drawing on the motivated cognition and moral disengagement literature, we illustrate how cognitive mechanisms coalesce to allow managers to soothe their moral (self-) concerns when grappling with these conundrums. Third, we show how motivated justice intentions ensuing from specific justice motives, moral emotions, and circles of moral regard predict the types of justice conundrums managers face and the paths they take to grapple with them.